Mathematical puzzle tales from Mount Olympus - Liu, A. C. F. (Boca Raton CRC Press, 2023)
"Mathematical Puzzle Tales from Mount Olympus uses fascinating tales from Greek Mythology as the background for introducing mathematics puzzles to the general public. A background in high school mathematics will be ample preparation for using this book, and it should appeal to anyone who enjoys puzzles and recreational mathematics. Features Combines the arts and science, and emphasizes the fact that mathematics straddles both domains. Great resource for students preparing for mathematics competitions, and the trainers of such students"--
Keywords: Mathematical recreations; Puzzles